The origins of african Plasmodium vivax; insights from mitochondrial genome sequencing - Culleton, Richard (2021)
Plasmodium vivax, the second most prevalent of the human malaria parasites, is estimated to affect 75 million people annually. It is very rare, however, in west and central Africa, due to the high prevalence of the Duffy negative phenotype in the human population. Due to its rarity in Africa, previous studies on the phylogeny of world-wide P. vivax have suffered from insufficient samples of African parasites. Here we compare the mitochondrial sequence diversity of parasites from Africa with those from other areas of the world, in order to investigate the origin of present-day African P. vivax. Mitochondrial genome sequencing revealed relatively little polymorphism within the African population compared to parasites from the rest of the world. This, combined with sequence similarity with parasites from India, suggests that the present day African P. vivax population in humans may have been introduced relatively recently from the Indian subcontinent. Haplotype network analysis also raises the possibility that parasites currently found in Africa and South America may be the closest extant relatives of the ancestors of the current world population. Lines of evidence are adduced that this ancestral population may be from an ancient stock of P. vivax in Africa.